Dialética das disputas: trabalho pedagógico a serviço da classe trabalhadora? - Maraschin, Mariglei Severo (2015)
This study is related to the School Practices and Public Policies research line of the Post-Graduation Course on Education at Federal University of Santa Maria/RS state/Brazil and was constructed from experiences at Kairós – Group of Researches and Studies on Work, Education and Public Policies. The research intention arrives from the observation that the increase of federal programs that integrate Professional Education (PE) and Youth and Adult Basic Education modality, in the last decade, brings these fields to the educational discussion and takes teachers, educational managers and researchers to evaluate and to dialogue about pedagogical work developed in these Programs. It is observed that not only the Youth and Adult Education (YAE) policies integrated to PE but also the pedagogical work made on the praxis of these courses were put into effect in context of a dialectic of disputes, understood as the different disputes – opposition and fight among conceptions and meanings about pedagogical work and disputes related to the place of policies for workers. In this process, the research has aimed to answer which meanings of work, technology and pedagogical work were made evident on pedagogical work of Youth and Adult Education (YAE) integrated to PE policies in a Federal Institution in RS state/Brazil and how they contribute to the arrangement of the dialectic of disputes context. The general aim is investigating, on dialectical perspective, the meaning(s) of work, technology and pedagogical work on the policies of Basic Education integrated to Professional Education, at Youth and Adult Education modality, in Federal Institutes/RS state/Brazil and how they contribute to the arrangement of a dialectic of disputes context around policies and pedagogical work, from 2005 to 2014. To construct this research, it was organized a theoretical background about Pedagogical work, about meanings and concepts of work, technology and working class, about the history of policies on PE integrated to YAE Basic Education modality, since 2005, mapping how the Brazilian programs developed, as PROEJA Médio, PROEJA Médio, PROEJA FIC, CERTIFIC, PRONATEC EJA and about the engagement of Federal Institutes with those policies. After this overview, it was worked with the hypothesis that critical meanings of work and technology were not made evident in pedagogical work with YAE integrated to PE policies and these ones were not available for working class, contributing to the arrangement of a dialectic of disputes context. The study was based on dialectical and historical materialism. Through content categories: disputes, meanings of movement of Brazilian PROEJA/RS courses, meanings of pedagogical work, meanings of work and technology, working class, time and pedagogical work; it was made analysis of content in discourses elaborated in interviews with education managers, focus group with teachers and teams, focus group with students and interlocution group with teacher from six campi of Federal Institutes of RS state/Brazil, two from each Institute. The study understood that the meanings of work and technology were not clear in pedagogical work of researched realities, except of one reality that has been spotlighted for the enforcement of integrated curriculum. It was also observed that there have not been worker class mechanisms of participation in the Federal Institutes of RS state/Brazil and that there are many disputes mapped on the practice, resulting on a question if disputes are for financial resource or they are disputes of conception and management. It was analyzed that this field has many possibilities of new studies and that pedagogical work and meetings construct meanings for PE integrated to YAE policy. It is proposed, thus, an enlargement of the agenda of public educational policies, investment on pedagogical work. This work makes possible actions, relations and transformations that were set up in dialectic of disputes context in which the critical and naive meanings of pedagogical work, work and technology are put in movement in an unfinished process. Therefore, considering the favorable side of disputes, it was believed on a management for pedagogical work, on pedagogical meetings and on necessary time for the integrated formation of working class.